O modelo alemão da Terapia do Esquema: conceituação, técnicas e aplicação clínica na Psicoterapia Infantil - Bizinoto, Jessica Ferrucci Suzuki (2015)
This study presents the conceptual and interventionist model of Schema Therapy for children and adolescents developed by Christof Loose in collaboration with psychotherapists in Germany, as an innovative proposal adapted of the Schema Therapy model proposed by Jeffrey Young. For this purpose, initially, a systematic review of Schema Therapy with children and adolescentes was performed who indicated that research focused from the period 2005-2015, whose publications are characterized by psychometric studies and adaptations of the Schema Inventory for children and from 2012 found publications directed to theoretical adaptations and psychotherapeutic intervention techniques for children in approach. The articles are more numerous, but are psychometric studies of scales. Publications on intervention are only avaiable in German book. The most methods of study are the psychometric and quasi-experimental, followed by case studies related intervention studies. From this literature review, this research focused on the appearance of the theoretical and practical bases of the German model Schematherapie für Kinder und Jungedlichen. This study describes protocols to guide parents and attend children and adolescentes and demonstrate that processo of evaluation, psychoeducation and a creative proposal with experiential techniques that work the imagination, the therapist meets the basic needs of parents and guides actions to healthier behavior. This initial study suggests that to the Brazilian culture some adaptations of techniques will be necessary, however, intervention protocols are promising and can make interventions for children and adolescents more effective.